A Flow Cytometric Approach to Assess RBC-Bound IgG Antibodies in Different Age Populations - Anwar Ullah; Lina Liu; Xia Qi; Hui Liu (Immunobiology)
Background: RBC-bound IgG antibody-mediated agglutination occurs when red blood cells (RBCs) cluster together due to the presence of antibodies or other contributing factors. This process could be favorable in the elderly population. Not only is it critical for blood typing procedures, but also plays a significant role in autoimmune hemolytic anemia, a condition characterized by escalated destruction of RBCs. Understanding these mechanisms are essential for precise diagnoses, ensuring the safety of blood transfusions, and facilitating laboratory testing protocols in clinical settings. Objective: This study explores to detect RBC-bound IgG antibodies in various age groups using flow cytometry method. Materials and methods: A total of 120 Serum samples were taken from different age groups of healthy individuals. In addation, 30 samples were obtained from individuals with autoimmune diseases, and another 30 samples were collected from healthy elderly individuals of the same ages. Serum (100 μL) were added in eppendorf tube containing equal amount of normal saline and 50 μL of 2 % RBC, mixed well and then kept in water bath at 37 °C for 30 min. After incubation, antihuman globulin (AHG) was added and checked for the index of agglutination (IAG) using flow cytometry method. A control sample was also analyzed using the same method. Results: Flow cytometry analysis revealed significant differences in IAG between younger individuals and the elderly (P-value 0.003), demonstrating a positive linear relationship. Interestingly, no agglutination was observed in the younger group, whereas elderly healthy individuals exhibited agglutination. Furthermore, significant differences were found between autoimmune disease patients and elderly healthy individuals of the same age groups (P-value 0.0001), with strong IAG in autoimmune patients compared to relatively less agglutination in the elderly population. Conclusion: Our study has successfully detected RBC-bound IgG antibodies in various age groups. Young age groups showed negative IAG while elderly individuals and patients with autoimmune diseases exhibited the presence of RBC-bound IgG antibodies.